Determination of precious and rare metals in minerals concentrates and tailings, using k_0 based instrumental neutron activation analysis - Torres, Blanca (2002)
Under the frame of CRP “Validation of nuclear techniques for analysis of precious and rare metals in mineral concentrates”, in order to improve the utilization of nuclear analytical techniques in terms of high accuracy and precision for the analysis of precious and rare metals in mineral concentrates, It was carried out the project “Determination of precious and rare metals in minerals concentrates and tailings, using k0 based instrumental neutron activation analysis” Au, Ag, were analysed in copper concentrates, Re in molybdenum concentrates and In and Ga in tails of zinc concentrates. To this effect, two in house secondary reference materials, i.e. a copper concentrate for the determination of precious metals at the trace levels and heavy mineral concentrate for the determination of lanthanides and actinides at minor trace levels, the CRP prepared and distributed among 8 participants of different countries.